Peningkatan Kompetensi Guru Matematika melalui Workshop Pendekatan Metakognitif - Nyimas Inda Kusumawati; Ali Syahbana; Rohman Rohman (Universitas Muhammadiyah Mataram, 2026)
Abstract: This community service program aimed to improve the pedagogical competence of mathematics teachers in implementing metacognitive approaches in the learning process at SMP Negeri 17 Palembang. The metacognitive approach is considered important in developing students’ reflective, independent, and systematic thinking skills. The implementation method consisted of preparation, workshop activities, mentoring, and monitoring and evaluation. The workshop was conducted through material presentations, discussions, case studies, and practical training in developing metacognitive-based lesson plans. The participants consisted of 19 mathematics teachers. Data were collected through observation, questionnaires, and document analysis. The results showed an improvement in teachers’ understanding and skills in designing metacognitive-based learning. A total of 57.9% of participants stated that the program was very beneficial, while 42.1% considered it beneficial. In addition, 53.6% of participants showed strong motivation to apply the metacognitive approach in their classrooms. The program also positively impacted teachers’ soft skills, such as reflective attitudes, openness to innovation, and collaboration, as well as their hard skills in developing instructional materials. Therefore, this community service program effectively supports the improvement of mathematics learning quality in partner schoolsAbstrak: Kegiatan pengabdian kepada masyarakat ini bertujuan untuk meningkatkan kompetensi pedagogis guru matematika dalam menerapkan pendekatan metakognitif pada proses pembelajaran di SMP Negeri 17 Palembang. Pendekatan metakognitif dipandang penting dalam membantu siswa mengembangkan kemampuan berpikir reflektif, mandiri, dan sistematis. Metode pelaksanaan kegiatan meliputi tahap persiapan, pelaksanaan workshop, pendampingan, serta monitoring dan evaluasi. Workshop dilaksanakan melalui kegiatan penyampaian materi, diskusi, studi kasus, dan praktik penyusunan Rencana Pelaksanaan Pembelajaran (RPP) berbasis metakognitif. Subjek kegiatan terdiri atas 19 guru matematika. Teknik pengumpulan data dilakukan melalui observasi, angket, dan analisis dokumen. Hasil kegiatan menunjukkan adanya peningkatan pemahaman dan keterampilan guru dalam merancang pembelajaran berbasis metakognitif. Sebanyak 57,9% peserta menyatakan kegiatan sangat bermanfaat dan 42,1% menyatakan bermanfaat. Selain itu, 53,6% peserta menunjukkan motivasi yang sangat tinggi untuk menerapkan pendekatan metakognitif di kelas. Kegiatan ini juga berdampak positif terhadap peningkatan softskill guru, seperti sikap reflektif, keterbukaan terhadap inovasi, dan kemampuan kolaborasi, serta peningkatan hardskill dalam pengembangan perangkat pembelajaran. Dengan demikian, kegiatan pengabdian ini efektif dalam mendukung peningkatan kualitas pembelajaran matematika di sekolah mitra.